2021
DOI: 10.1038/s41418-021-00808-w
|View full text |Cite
|
Sign up to set email alerts
|

RNF20 and RNF40 regulate vitamin D receptor-dependent signaling in inflammatory bowel disease

Abstract: Despite the identification of several genetic factors linked to increased susceptibility to inflammatory bowel disease (IBD), underlying molecular mechanisms remain to be elucidated in detail. The ubiquitin ligases RNF20 and RNF40 mediate the monoubiquitination of histone H2B at lysine 120 (H2Bub1) and were shown to play context-dependent roles in the development of inflammation. Here, we aimed to examine the function of the RNF20/RNF40/H2Bub1 axis in intestinal inflammation in IBD patients and mouse models. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…For instance, TNFAIP3 in ILC1 and activated DC is induced by TNFα, as are IRF1 (and related interferon-pathway genes) in all of these cell types and STAT1 , leading to an autocrine loop of inflammation [ 38 ]. Similarly, the induction of HLA-C, which we have shown in all of these populations, can be explained via induction by TNFα [ 39 ]. The importance of these expression patterns is highlighted by the application of TNFα inhibitors as a mainstay therapy for over 20 years [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 92%
“…For instance, TNFAIP3 in ILC1 and activated DC is induced by TNFα, as are IRF1 (and related interferon-pathway genes) in all of these cell types and STAT1 , leading to an autocrine loop of inflammation [ 38 ]. Similarly, the induction of HLA-C, which we have shown in all of these populations, can be explained via induction by TNFα [ 39 ]. The importance of these expression patterns is highlighted by the application of TNFα inhibitors as a mainstay therapy for over 20 years [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 92%
“…Treatment with a chemical carcinogen and DSS resulted in more colorectal polyps in Rnf20 +/− mice, which often progressed to inflammation-associated colorectal cancer [ 193 ]. In correspondence with these results, samples from human patients with ulcerative colitis, Crohn’s disease, and colorectal tumors, showed downregulation of RNF20/40 and H2BK120ub in both epithelium and stroma [ 193 , 200 ]. Similarly, when Rnf20 or Rnf40 were conditionally deleted in the mouse intestine, spontaneous colorectal inflammation occurred, and these knockout mice displayed significantly decreased survival [ 200 ].…”
Section: The Importance Of Rnf20/40 and H2bk120ub In Tissue Developme...mentioning
confidence: 76%
“…In correspondence with these results, samples from human patients with ulcerative colitis, Crohn’s disease, and colorectal tumors, showed downregulation of RNF20/40 and H2BK120ub in both epithelium and stroma [ 193 , 200 ]. Similarly, when Rnf20 or Rnf40 were conditionally deleted in the mouse intestine, spontaneous colorectal inflammation occurred, and these knockout mice displayed significantly decreased survival [ 200 ]. Colon length was also decreased in these mice, and their colons showed severe epithelial damage and lymphoid infiltrates, while heterozygous Rnf20 or Rnf40 mice did not show similar phenotypes.…”
Section: The Importance Of Rnf20/40 and H2bk120ub In Tissue Developme...mentioning
confidence: 76%
“…Besides, vitamin D condition was considered as one of the environmental or dietary associations with the activity of IBD ( Lim et al, 2005 ). And a study found that the monoubiquitination of histone H2B can promote the inflammation through decreased Vitamin D Receptor activity, and which maybe the biomarker of whether to receive Vitamin D supplements of IBD patients ( Kosinsky et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%